(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Compressor is used to get high pressure air for much industrial and commercial purpose. The triangular air compressor with common compression chamber is a reciprocating type compressor, which delivers air at high pressure with less vibration and less power consumption than the existing ones. Triangular air compressor with common compression chamber uses three cylinders and the entire cylinder and all the cylinders will have their own connecting red, crank shaft, pistons and chain sprockets and it is driven by a chain drive. During operation the pistons will move in phase from BDC to TDC and hence air is compressed in the common compression head. This common in the compression chamber will have one inlet and outlet valve. From this valve air is intake and delivered. The common compression head will be being triangular shape with angle of 60* from one side to other